KKN Mandiri Pada Masa Pandemi Covid-19 dengan tema Pengelolaan Data Desa di Desa Saosina Kecamatan Adonara Timur Kabupaten Flores Timur - Naima Sulaiman; Maria Helena Carolinda Dua Mea (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
In 2021, the University of Flores Community Service Program is carried out in the New Normal period, with students carrying out the Community Service Program independently in their respective villages. The author chose the village of Saosina, which is located on Adonara Island, which is part of the East Flores Regency area. Village data collection is not carried out optimally due to a lack of village officials, limited village facilities, and the absence of a village website. The author managed the data of Saosina village using the methods of observation, interviews, and documentation. The main work program at Independent Community Service Program in Saosina Village is to deal with issues that arise in the management of village data administration, such as data collection, input, and the creation of community documents (family cards, birth certificates, transfer letters). Outside of the theme, activities included the distribution of basic food assistance, the production of trash cans, and the cleaning of village offices. It is hoped that the Village Government will be able to continue the programs started by KKN students and apply the concept of implementing activities as done by KKN students. In the face of the digital era 4.0, the Saosina Village Government should be able to create a special website for the Saosina Village Government on the internet that contains village information and statistics about the Saosina village.